Success of DeepSeek and potential benefits of free access to AI for global-scale use - Okaiyeto, Samuel Ariyo; Bai, Junwen; Wang, Jun; Mujumdar, Arun S; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2025)
The introduction of DeepSeek R1, an AI language model developed by the Chinese AI lab DeepSeek, has made a significant impact in the tech world[1]. Within a week of its release, the app surged to the top of download charts, triggered a massive $1 trillion (£800 billion) sell-off in tech stocks, and prompted intense reactions from Silicon Valley. As artificial intelligence (AI) continues to evolve rapidly, it has become a cornerstone of global technological progress, with nations vying to push the boundaries of what AI can achieve. While companies like OpenAI and Nvidia in the United States have led AI research and deployment, the rise of DeepSeek represents a noteworthy shift in the landscape. DeepSeek’s innovative use of reinforcement learning (RL) and model distillation has significantly enhanced the reasoning capabilities of large language models (LLMs), while also advancing more efficient algorithms that reduce computing resource and energy consumption. This paper explores the factors behind DeepSeek’s success and its broader impact on making AI more accessible and efficient, especially for the developing world. By contributing to AI’s global accessibility, China’s advancements hold great potential to positively transform diverse sectors, from agriculture to energy and healthcare, supporting the goal of peaceful coexistence and improving life around the globe.Key words: AI, DeepSeek, reinforcement learning, model distillation, free access, global-scale utilizationDOI: 10.25165/j.ijabe.20251801.9733Citation: Okaiyeto S A, Bai J W, Wang J, Mujumdar Arun S, XiaoH W. Success of DeepSeek and potential benefits of free access toAI for global-scale use. Int J Agric & Biol Eng, 2025; 18(1):304–306.